Assessment of students’ understanding of physical phenomena through argumentative qualities of written texts (2023)
RESUMEN: We present a qualitative study aimed at devising a theoretical-methodological tool to assess students’ conceptual understanding of physical phenomena through the argumentative qualities of their written texts. The proposed relationship between argumentation and understanding is elaborated through the notions of knowledge, purposes, methods, and communicative forms, as well as the use of data, warrants, modal qualifiers, claims, and rhetorical resources. In order to exemplify the tool’s use, the current understanding of six students attending a physics seedbed course was assessed according to four levels: naïve, novice, apprentice, and mastery. We then discuss the possibilities and limitations of the tool and the need to broaden the assessment of students’ understanding to include argumentative tasks in the classroom.